The Effectiveness Analysis of the Implementation of Restorative Justice in the Criminal Justice System in Bungo Regency: An Islamic Law Perspective - Adha Fristanto; Risnita Risnita; Yuliatin Yuliatin; Abdul Halim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to examine the implementation of restorative justice within Bungo Regency's criminal judicial system from the perspective of Islamic law. Although restorative justice has been formally adopted in Indonesia through various regulations, its application at the regional level remains an important issue that requires careful attention. The study employs a juridical-empirical research design with a qualitative approach. Data was gathered through observations, in-depth interviews with law enforcement, religious leaders, victims, and offenders, and document analysis. The analysis integrates perspectives from both positive law and Islamic law, particularly focusing on the principles of qiṣāṣ–diyāt, ṣulḥ, ‘afw, ta‘zīr, and maqāṣid al-sharī‘ah. The findings indicate that restorative justice is used in certain criminal cases during the investigative phase in Bungo Regency. However, its effectiveness is limited by factors such as varying levels of readiness among victims and offenders, insufficient technical regulations, community resistance, and inconsistent understanding among law enforcement. From an Islamic law perspective, restorative justice aligns well with Islamic justice principles, particularly those emphasizing public welfare, forgiveness, and restoration. The study concludes that restorative justice is a contemporary manifestation of principles deeply rooted in Islamic legal tradition and not a contradiction of Islamic law. To improve its application, enhancing law enforcement competence, engaging religious and community leaders, and integrating Islamic legal principles into criminal justice policies are essential.